(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
In order to improve learning outcomes and student engagement, this study investigates a model of motivation and goal-setting procedures within the context of higher education in Malaysia. The research, which is based on theories of motivation and self-regulated learning, highlights internal and extrinsic motivators, behaviors related to goal-setting, and successful learning techniques as crucial elements impacting students’ academic achievement. Data from undergraduates at six private universities in Selangor, Malaysia was gathered using a mixed-methods strategy that combined quantitative surveying with qualitative in-depth interviews. Qualitative research showed that students’ learning habits were impacted by cultural and institutional factors, whereas quantitative research showed that students’ motivation, goal clarity, and academic achievement were all significantly correlated. The findings highlight the significance of tailored frameworks for goal-setting and adaptive learning tactics in creating a nurturing classroom climate. In order to help make Malaysia’s higher education system more effective and inclusive, this report provides educators and policymakers with practical ideas for targeted reforms.